2013
DOI: 10.1037/a0031893
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HCN channels within the periaqueductal gray attenuates neuropathic pain in rats.

Abstract: Peripheral and spinal hyperpolarization-activated cyclic nucleotide-gated cation (HCN) channels play important roles in neuropathic pain by regulating neuronal excitability. However, the participation of HCN channels in the ventral-lateral periaqueductal gray (vlPAG) during neuropathic pain states has not been clarified. To investigate the role of vlPAG HCN channels in neuropathic pain, the authors developed a chronic constriction injury (CCI) model. By using western blot analysis, they detected the upregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Xie et al observed increased Ih in primary afferent neurons of rats with nerve CCI-induced spontaneous pain (Xie et al 2005). Dalle et al reported that blockade of Ih in peripheral neurons of rats with partial SNL alleviated mechano-allodynia (Dalle et al 2005), while other studies in animal models of neuropathic pain have also observed reductions in mechanical allodynia and thermal hyperalgesia with pharmacologic inhibition of Ih (Du et al 2013a;Tibbs et al 2013;Young et al 2014). Wickenden et al found that HCN channels in medium and large-sized DRG neurons of injured primary sensory nerves responded preferentially to nociceptive discharges (Wickenden et al 2009).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Xie et al observed increased Ih in primary afferent neurons of rats with nerve CCI-induced spontaneous pain (Xie et al 2005). Dalle et al reported that blockade of Ih in peripheral neurons of rats with partial SNL alleviated mechano-allodynia (Dalle et al 2005), while other studies in animal models of neuropathic pain have also observed reductions in mechanical allodynia and thermal hyperalgesia with pharmacologic inhibition of Ih (Du et al 2013a;Tibbs et al 2013;Young et al 2014). Wickenden et al found that HCN channels in medium and large-sized DRG neurons of injured primary sensory nerves responded preferentially to nociceptive discharges (Wickenden et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…For example, increased expression of HCN1 and HCN2 and a shift in the activation curve of Ih have been reported to occur in a rat model of neuropathic pain (Du et al 2013a, b), while HCN2 knockout mice have been found to show no neuropathic pain, in response to thermal or mechanical stimuli, after a nerve lesion (Emery et al 2011). Furthermore, pharmacologic inhibition of Ih in peripheral nociceptive neurons has been observed to reduce mechanical allodynia and thermal hyperalgesia in animal models of neuropathic pain (Du et al 2013a;Tibbs et al 2013;Young et al 2014), alleviate inflammation-induced hypersensitivity of the rat temporomandibular joint (Hatch et al 2013), and augment activity-dependent conduction velocity slowing in axotomized C-fibers (Mazo et al 2013). Thus, there is substantial evidence that enhanced HCN channel function may contribute to neuropathic pain.…”
Section: Introductionmentioning
confidence: 94%
“…HCN3 is detected at low levels in the olfactory bulb and some areas of the hypothalamus, whereas HCN4 is found in restricted brain areas such as the nucleus of the lateral olfactory tract and thalamus [87,88]. This review will focus on the role of HCN channels in the PNS; for more information on CNS functions, including supraspinal pain pathways, readers are referred to other recent studies [85,86,[93][94][95][96]. This review will focus on the role of HCN channels in the PNS; for more information on CNS functions, including supraspinal pain pathways, readers are referred to other recent studies [85,86,[93][94][95][96].…”
Section: Decreased Neuronal Activitymentioning
confidence: 99%
“…Forskolin, which elevates intracellular cAMP, mimics CCI-induced changes in neuronal excitability in vIPAG. Furthermore, ZD7288, a HCN blocker, attenuated spontaneous EPSCs and reversed the effects of forskolin [105].…”
Section: New Targets In Neuropathic Pain Treatmentmentioning
confidence: 99%